1994
DOI: 10.1002/ijc.2910590308
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of tissue inhibitor of metalloproteinase‐2 (TIMP‐2) in the stroma of breast carcinomas correlates with tumor recurrence

Abstract: The 72-kDa (MMP-2, gelatinase A) and the 92-kDa (MMP-9, gelatinase B) matrix metalloproteinases have been associated with tumor cell invasion and metastasis. Immunohistological staining of MMP-2 and MMP-9, basal lamina collagen IV and TIMP-2 were performed on frozen sections of 83 invasive breast carcinomas. MMP-2 and MMP-9 were associated with neoplastic cell plasma membrane in 72% of cases and exhibited inter-tumoral variability of staining intensity. MMP-2 and MMP-9 staining was not correlated with presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
83
1
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 13 publications
15
83
1
1
Order By: Relevance
“…Pro-MMP-2 in the ternary complex is activated by MT1-MMP that is free from TIMP-2. [25][26][27] Recently, some studies reported that TIMP-2 plays a positive role in invasion and metastasis in carcinoma of the breast, 28 lung, 29 colon, 30 and bladder. 31 The current study demonstrated that both MMP-2 and TIMP-2 were detected mostly on the tumor cell surface and cytoplasm of thymomas and that they stained more strongly in border areas between the tumor and the stroma, which was the invasive area, compared with the central area of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-MMP-2 in the ternary complex is activated by MT1-MMP that is free from TIMP-2. [25][26][27] Recently, some studies reported that TIMP-2 plays a positive role in invasion and metastasis in carcinoma of the breast, 28 lung, 29 colon, 30 and bladder. 31 The current study demonstrated that both MMP-2 and TIMP-2 were detected mostly on the tumor cell surface and cytoplasm of thymomas and that they stained more strongly in border areas between the tumor and the stroma, which was the invasive area, compared with the central area of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity was visualized by successive incubations with alkaline phosphatase-conjugated goat anti-mouse (or antirabbit for TIMP-1) IgG and color developing substrates. The preparation of mAb against human progelatinase A, progelatinase B and TIMP-2 were previously described [26,27]. The rabbit polyclonal antiserum against human TIMP-1 was kindly provided by Dr. Chua (Wayne State University).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…The findings seem to be contradictory to the proposed role of TIMP-1 as a tumour metastasis suppressor: if TIMP-1 acts as a functional inhibitor of tumour invasion and metastasis, its expression should inversely correlate with the aggressiveness of thyroid tumours. Indeed, such an inverse association has been documented in several (Albini et al, 1991;DeClerck et al 1991DeClerck et al , 1992Ponto et al, 1991;Khoka et al, 1992Khoka et al, , 1994Montgomery et al, 1994) but not all (Kussakowska et al, 1991;Lu et al, 1991;Visscher et al, 1994aVisscher et al, , 1994bNakana et al, 1995;Zeng et al, 1995;Grignon et al, 1996) human and mouse tumours. One possible explanation for increased TIMP-1 expression in advanced stages of thyroid carcinoma is that it may represent a secondary event, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by the low TIMP-1 expression in both NPA and SW579 thyroid cancer cell lines that are derived from poorly differentiated thyroid carcinomas without stroma contamination. Several studies have demonstrated that increased TIMP-1 or TIMP-2 expression in advanced stages of malignancy derives predominantly from stroma cells rather than from cancer cells themselves (Kossakowska et al, 1991;Visscher et al, 1994b;Zeng et al, 1995;Grignon et al, 1996). In the study of elevated TIMP-1 mRNA levels in non-HodgkinÕs lymphoma, Kossakowska et al (1991) showed by in situ hybridization that TIMP-1 transcripts were not localized to the malignant lymphocytes, but instead were present within stromal cells which account for only 20% of the total cells in each sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation